1988
DOI: 10.1016/0887-6177(88)90024-8
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous and successive cognitive processes in brain damaged adults: Hemispheric and anterior-posterior effects

Abstract: The relationship between simultaneous and successive processing and their assumed underlying neuro-anatomical structures was examined. According to the model of Das, Kirby, and Jarman (1975, 1979) simultaneous processing, occurs mainly in the posterior parts of the brain (parieto-occipital areas) and successive processing in anterior regions of the brain (fronto-temporal areas). The theory of lateralized hemispheric specialization suggests differences in processing due to right-left hemispheric differences. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In a large adult sample of brain-injured patients Aysto and Hanninen found that left hemisphere-lesioned patients were significantly more impaired than the right hemisphere counterparts on successive processing 89. Similarly, a trend for regional specificity was also found such that the levels of performance of left posterior patients was less than that of left anterior patients, that these were less than that of right anterior patients, and finally that these were all less than that of right posterior patients.…”
Section: Successive Processing: Neural Correlatesmentioning
confidence: 83%
See 4 more Smart Citations
“…In a large adult sample of brain-injured patients Aysto and Hanninen found that left hemisphere-lesioned patients were significantly more impaired than the right hemisphere counterparts on successive processing 89. Similarly, a trend for regional specificity was also found such that the levels of performance of left posterior patients was less than that of left anterior patients, that these were less than that of right anterior patients, and finally that these were all less than that of right posterior patients.…”
Section: Successive Processing: Neural Correlatesmentioning
confidence: 83%
“…The evidence taken as a whole seems to be concordant with this dual processing hypothesis despite the fact that the DN-CAS does not have a nonverbal sequencing tasks included within the standardization battery. Aysto and Hanninen found that their successive factor was sensitive to left hemisphere lesions; however all their successive tasks were verbal 89. Kim and colleagues found that verbal and nonverbal sequencing were impaired by left and right hemisphere lesions, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations